Penggunaan Media Aksara Jawa Digital Dalam Pembelajaran Menulis Aksara Jawa - Ismiati; Darni; Resdianto Permata Raharjo; Anas Ahmadi (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Javanese script is a cultural heritage of the Indonesian nation that has high historical, philosophical, and aesthetic value. However, in the context of education, student interest in learning Javanese script is still relatively low. Low student interest results in low Javanese script writing skills in students. Lack of Javanese script writing skills results in low student learning outcomes. This occurs because students have difficulty distinguishing the form of Javanese script that is almost similar, the lack of reading sources containing Javanese script, the lack of use of Javanese script in everyday life and the lack of learning media that is adaptive to the development of digital technology. These conditions require a solution, so in this study Rajagita Media becomes a solution to the problem of students' lack of skills in writing Javanese script and the low learning outcomes of writing Javanese script students of SMP Negeri 7 Madiun. This study aims to determine the process of implementing Rajagita media in learning to write Javanese script for grade IX students of SMP Negeri 7 Madiun which influences students' writing skills. This study used a quantitative approach with an experimental method, namely a Quasi-Experimental Design, applying a